2010
DOI: 10.1007/s10585-010-9323-2
|View full text |Cite
|
Sign up to set email alerts
|

Small breast epithelial mucin (SBEM) has the potential to be a marker for predicting hematogenous micrometastasis and response to neoadjuvant chemotherapy in breast cancer

Abstract: To investigate the potential role of small breast epithelial mucin (SBEM) as a marker for detecting hematogenous micrometastasis in breast cancer and explore its clinical significance in neoadjuvant chemotherapy. SBEM protein expression in 82 tissue specimens of primary breast cancer was detected using immunohistochemistry (IHC), and SBEM expression in peripheral blood (PB) samples of 109 primary breast cancer patients (94 cases at stage I-III, 15 cases at stage IV) was detected by flow cytometry (FCM) and rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Several studies have now shown that MUCL1 expression strongly correlates with higher tumor grade, 4 TNM (tumor, node, metastases) staging and lymph node metastasis. 3, 5 Most recently, it was shown that high MUCL1 expression is significantly correlated with high recurrence and death rates in triple negative breast cancer patients. 6 …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have now shown that MUCL1 expression strongly correlates with higher tumor grade, 4 TNM (tumor, node, metastases) staging and lymph node metastasis. 3, 5 Most recently, it was shown that high MUCL1 expression is significantly correlated with high recurrence and death rates in triple negative breast cancer patients. 6 …”
Section: Introductionmentioning
confidence: 99%
“…So, we examined SBEM levels in FFPE tissue sections by IHC test and then analyzed the correlation of SBEM expression with DFS and OS. Liu et al reported that SBEM protein expression correlated with tumor size, TNM staging and lymph node metastasis [9]. Ki67 is used to assess the prognosis of cancer patients [23].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, SBEM expression in PB (Peripheral blood) of breast cancer patients was markedly higher than that of healthy donors and other cancer patients [9]. Determination of SBEM protein in tissue and mRNA expression in PB of TNBC patients maybe helpful for early diagnosis, choice of treatment, decision of the degree of malignancy and risk prediction of recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations